Pengembangan Aplikasi Teknologi Augmented Reality untuk Mendukung Konsep Smart City Daerah Istimewa Yogyakarta - Sahria, Yoga; Haryoko, Haryoko; Piskonata, Yogi Piskonata (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This research develops Augmented Reality (AR) applications at Sonobudoyo Museum as part of the Smart City concept in Yogyakarta. Museum digitization aims to improve visitor experience through interactive technology. The AR application developed allows users to access museum collection information in the form of 3D visualization, video, and text via mobile devices. The research method uses Research and Development (R&D) with the Analyze, Design, Develop, Implement, Evaluate development model and the MDLC (Multimedia Development Life Cycle) approach. Evaluation was conducted based on visitor responses related to ease of use, attractiveness, and cultural understanding. The results showed that the application of AR increased visitor engagement and satisfaction and supported public services in the tourism and cultural education sectors. With a System Usability Scale (SUS) score of 88, this application is categorized as “excellent”. AR technology is proven to be effective in preserving and promoting local culture and has the potential to be applied more widely in the Smart City ecosystem.Keywords: Augmented Reality; Sonobudoyo Museum; Smart Cities; Education Culture and technology. AbstrakPenelitian ini mengembangkan aplikasi Augmented Reality (AR) di Museum Sonobudoyo sebagai bagian dari konsep Smart City di Yogyakarta. Digitalisasi museum bertujuan meningkatkan pengalaman pengunjung melalui teknologi interaktif. Aplikasi AR yang dikembangkan memungkinkan pengguna mengakses informasi koleksi museum dalam bentuk visualisasi 3D, video, dan teks melalui perangkat seluler. Metode penelitian menggunakan Research and Development (R&D) dengan model pengembangan Analyze, Design, Develop, Implement, Evaluate serta pendekatan MDLC (Multimedia Development Life Cycle). Evaluasi dilakukan berdasarkan tanggapan pengunjung terkait kemudahan penggunaan, daya tarik, dan pemahaman budaya. Hasil penelitian menunjukkan bahwa penerapan AR meningkatkan keterlibatan dan kepuasan pengunjung serta mendukung layanan publik di sektor pariwisata dan edukasi budaya. Dengan skor System Usability Scale (SUS) 88, aplikasi ini masuk kategori "excellent". Teknologi AR terbukti efektif dalam melestarikan dan mempromosikan budaya lokal serta berpotensi diterapkan lebih luas dalam ekosistem Smart City.